2008
DOI: 10.1016/j.socscimed.2008.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and health: The role of subjective social status

Abstract: Studies have suggested that subjective social status (SSS) is an important predictor of health. This study examined the link between SSS and health in old age and investigated whether SSS mediated the associations between objective indicators of socioeconomic status and health. It used crosssectional data from the second wave (2004-05) of the English Longitudinal Study of Ageing, which were collected through personal interviews and nurse visits. The study population consisted of 3368 men and 4065 women aged 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
549
7
20

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 587 publications
(614 citation statements)
references
References 39 publications
38
549
7
20
Order By: Relevance
“…Previous studies have shown that physical activity remained significantly related to incident diabetes after adjustment for a single measure of SES (typically education [16][17][18] but also occupational class [19]). Our study has accounted in a fuller way for SES by adjusting models for both education and total wealth, which is one of the best measures of SES for older people [20], and thus has more convincingly shown that the significant association between physical activity and incident diabetes is not an artefact of residual confounding because of inadequate adjustment for SES.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown that physical activity remained significantly related to incident diabetes after adjustment for a single measure of SES (typically education [16][17][18] but also occupational class [19]). Our study has accounted in a fuller way for SES by adjusting models for both education and total wealth, which is one of the best measures of SES for older people [20], and thus has more convincingly shown that the significant association between physical activity and incident diabetes is not an artefact of residual confounding because of inadequate adjustment for SES.…”
Section: Discussionmentioning
confidence: 92%
“…Health outcomes linked to subjective socioeconomic position included self-rated health (SRH; Demakakos et al, 2008;Singh-Manoux et al, 2005), depression (Demakakos et al, 2008;Sakurai et al, 2010;Singh-Manoux et al, 2003), nurse-rated health (Nobles et al, 2013), cortisol (Adler et al, 2000;Wright and Steptoe, 2005), and mortality rates (Kopp et al, 2004). While some studies showed that the association between subjective socioeconomic status and health was explained when accounting for objective markers of SES, at least for some outcomes (Singh-Manoux et al, 2003), the majority of studies suggest that subjective SES is associated with health even after controlling for objective SES.…”
Section: The Subjective Ses-health Relationshipmentioning
confidence: 99%
“…Terms that are sometimes used synonymously are perceived social position (Garbarski, 2010) and subjective social status (Adler et al, 2000;Demakakos et al, 2008). The great recent interest in subjective SES among public health researchers has two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…16 In studies of adults of all ages, lower SSS is associated with worse baseline self-rated health and health status. [11][12][13][14][17][18][19] While some studies find that the associations between subjective social status and health remain after accounting for objective measures of SES, 11,18 others do not. 19 To our knowledge, the only longitudinal study of subjective social status and health was conducted in British civil servants ages 35-55 years 10 and found that SSS was significantly associated with worse 3-year scores in psychological distress, the SF-36, and self-rated health.…”
Section: Introductionmentioning
confidence: 99%